The Role of Microbial Factors in the Pathogenesis of Male Infertility: A Literature Review - Piotr Rzyczniok; Aneta Rasińska; Weronika Rasińska; Anna Rzyczniok; Justyna Matusik; Natalia Pasierb; Sebastian Kupisiak; Aneta Rostkowska; Paulina Bala; Anna Rebizak; Justyna Jachimczak; Mateusz Kopczyński (Quality in Sport)
Purpose: Male infertility is a multifactorial condition with microbial infections emerging as significant yet under-recognized contributors. This review aims to explore the role of gram-positive and gram-negative bacteria in male infertility and to examine the intrinsic defense mechanisms of the male reproductive tract that are critical in preventing microbial invasion and preserving fertility.